Factors associated with the follow-up of high risk infants discharged from a neonatal intensive care unit - Seung Hyun Shin; Jin A Sohn; Ee-Kyung Kim; Seung Han Shin; Han-Suk Kim; Jin A Lee (Pediatrics and Neonatology)
Background: The study aimed to identify factors associated with compliance to follow-up (FU) appointments among infants following their discharge from the neonatal intensive care unit (NICU). Methods: This retrospective cohort study reviewed 657 infants (birth weight <1500 g or gestational age [GA] <32 weeks), born between 2011 and 2015. A total of 525 eligible infants were classified into two groups: the compliant group (n = 360), who attended clinics from 18 to 24 months, and the non-compliant group (n = 165), who were lost to FU before 18 months. Results: The non-compliant group was more likely to have higher usage rate of assisted reproductive technology (p = 0.023), GA (p < 0.001), weight (p < 0.001), height (p < 0.001), and head circumference (p < 0.001) at birth. The sibling number was higher in the non-compliant group (p = 0.011). Moreover, the non-compliant group demonstrated higher Apgar scores at 1 min and 5 min (p = 0.002 and p = 0.031, respectively). The compliant group was more likely to live in metropolitan or larger cities with a borderline significance (p = 0.056).Furthermore, the non-compliant group was less likely to suffer from respiratory distress syndrome (p < 0.001), patent ductus arteriosus (p = 0.002), retinopathy of prematurity (p = 0.007), necrotizing enterocolitis (p = 0.019), and bronchopulmonary dysplasia (p < 0.001). Moreover, it demonstrated lower postmenstrual age at discharge (p = 0.005) and a shorter length of stay in the NICU (p < 0.001). The compliance with FU appointment varied with the assigned doctor (p < 0.001).The multivariate regression analysis mentioned that the birth weight (OR = 0.903), residence in metropolitan or larger cities (OR = 1.495), and an experience of magnetic resonance imaging (OR = 1.920) were associated with compliance. The compliance to FU appointments was different according to the assigned doctor at admission (OR = 0.357). Conclusion: The birth weight, residence in metropolitan or larger cities, an experience of MRI, and the assigned doctors were associated with compliance to FU at a corrected age of 18–24 months.